Political Participation of Women in Gram Panchayat: A Study of Silinda 1.No Gram Panchayat (International Journal of Scientific Research and Management (IJSRM), 2017)
Political participation simply refers to the way through which the citizens of a country take part in the electoral as well as in policy making process. In other words, political participation is a way or a process through which the aspirations and needs of the people can be represented. Generally, the term “political participation” refers to those voluntary activities by which members of a society share in the selection of rulers and directly or indirectly in the formation of public policy. These activities include casting votes, seeking information, holding discussions, attending meetings, staging strikes and demonstrations, communicating with the legislators and the like. Women constitute more or less than half of the population of any country. Women have to recognize, collectively and critically, the forces that limit them and to work collectively and continuously to change the unequal power structure. The family, community and state should together create a situation wherein elected women representatives act effectively in PRIs. They need to be endowed with capacities and incentives to tackle the emerging challenges after entering into panchayat system. More favorable environment should be created which would enable the women to play more effective role in the decentralized development. Above all, the Gram Panchayats should act more actively and vigorously. In this gram panchayat members are leading in economic planning, agriculture and resource development, education and health monitoring, household industry monitoring etc